What is the role of quality circles in strategies to optimise antibiotic prescribing? A pragmatic cluster-randomised controlled trial in primary care. Issue 3 (1st June 2007) - van Driel, M L; Coenen, S; Dirven, K; Lobbestael, J; Janssens, I; Van Royen, P; Haaijer-Ruskamp, F M; De Meyere, M; De Maeseneer, J; Christiaens, T
Abstract : Objective: To evaluate the effect on antibiotic prescribing of an intervention in existing local quality circles promoting an evidence-based guideline for acute rhinosinusitis. Design: A pragmatic cluster-randomised controlled trial comparing standard dissemination of the guideline by mail with an additional strategy using quality circles. Setting: General practice in Flanders, Belgium. Participants: General practitioners (GPs) in 18 local quality circles were randomly allocated to two study arms. All GPs received the guideline by mail. GPs in the nine quality circles allocated to the intervention arm received an additional group intervention, which consisted of one self-led meeting using material introduced to the group moderator by a member of the research team. Main outcome measures: Adherence to the guideline was measured as differences in the proportion of antibiotic prescriptions, including the choice of antibiotic, between the two study arms after the intervention period. GPs registered their encounters with patients presenting with signs and symptoms of acute rhinosinusitis in a booklet designed for the study. Results: A total of 75 doctors (29% of GPs in the participating quality circles) registered 408 consultations. In the intervention group, 56.9% of patients received an antibiotic compared with 58.3% in the control group. First-choice antibiotics were issued in 34.5% of antibiotic prescriptions in the intervention group compared with 29.4% in the control group. After adjusting for patient and GP characteristics, the ORadj for antibiotics prescribed in the intervention arm compared with the control arm was 0.63 (95% CI 0.29 to 1.37). There was no effect on the choice of antibiotic (ORadj 1.07, 95% CI 0.34 to 3.37). Conclusion: A single intervention in quality circles of GPs integrated in the group's normal working procedure did not have a significant effect on the quality of antibiotic prescribing. More attention to the context and structure of primary care practice, and insight into the process of self-reflective learning may provide clues to optimise the effectiveness of quality circles.